Tension Sensor Based on Fluorescence Resonance Energy Transfer Reveals Fiber Diameter-Dependent Mechanical Factors During Myelination - Shimizu, Takeshi; Murakoshi, Hideji; Matsumoto, Hidetoshi; Ichino, Kota; Hattori, Atsunori; Ueno, Shinya; Ishida, Akimasa; Tajiri, Naoki; Hida, Hideki (Frontiers in Cellular Neuroscience, 2021)
Oligodendrocytes (OLs) form a myelin sheath around neuronal axons to increase conduction velocity of action potential. Although both large and small diameter axons are intermingled in the central nervous system (CNS), the number of myelin wrapping is related to the axon diameter, such that the ratio of the diameter of the axon to that of the entire myelinated-axon unit is optimal for each axon, which is required for exerting higher brain functions. This indicates there are unknown axon diameter-dependent factors that control myelination. We tried to investigate physical factors to clarify the mechanisms underlying axon diameter-dependent myelination. To visualize OL-generating forces during myelination, a tension sensor based on fluorescence resonance energy transfer (FRET) was used. Polystyrene nanofibers with varying diameters similar to neuronal axons were prepared to investigate biophysical factors regulating the OL-axon interactions. We found that higher tension was generated at OL processes contacting larger diameter fibers compared with smaller diameter fibers. Additionally, OLs formed longer focal adhesions (FAs) on larger diameter axons and shorter FAs on smaller diameter axons. These results suggest that OLs respond to the fiber diameter and activate mechanotransduction initiated at FAs, which controls their cytoskeletal organization and myelin formation. This study leads to the novel and interesting idea that physical factors are involved in myelin formation in response to axon diameter.